STRENGTHENING THE POTENTIAL OF THE INVESTMENT CLIMATE OF THEREPUBLIC OF KAZAKHSTAN (Промышленный Транспорт Казахстан, 2025)
This article proposes policy alternatives to address the ineffectiveness of implementingmeasures to improve the investment climate in Kazakhstan to attract investors.In order to assess the above alternatives, five criteria selected - efficiency, implementationcost, political acceptability, public support, and time of implementation.